Pengaruh Tax Avoidance, Investment Opportunity Set, dan Manajemen Aset Terhadap Nilai Perusahaan - Wahyu Nur Rohmah (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
ABSTRACT This study aims to determine the effect of tax avoidance, investment opportunity set, and asset management on corporate value. The data source used is secondary data. The sample in this research is manufacturing company miscellaneous industry sector period 2012-2016. The sampling technique used purposive sampling to get 12 companies. The data in this study using multiple regression with SPSS program version 17.0. The results showed that tax avoidance had a significant negative effect on firm value with t value of -2.197 and significance level of 0.002. Investment opportunity set positively affects the value of the company with t arithmetic 8.686 and the level of significance 0.000. Asset management does not affect the value of the company with t arithmetic 0.80 and significance level 0.936. Adjusted R Square value of 0.666 can be interpreted that the contribution of all independent variables in explaining the dependent variable is 66.6%.